Influência da mudança organizacional na percepção dos papéis desempenhados no trabalho: o caso do arsenal de Marinha do Rio de Janeiro - Brandão, Sergio Miranda (2003)
This research intends to analyze the influence of organizational change which occurred in the Arsenal de Marinha do Rio de Janeiro (AMRJ) about the perception in relation of the roles played by their employees of the tactical and operational leveI in concern with their believes and values upon their jobs. This research constitutes a case study and took place in field research in a qualitative way and therefore the data was carefully analyzed in a descriptive-interpretative mode. Primary data \Vere collected from analysis on documents such as reports, norms, publications and internaI rules; and the secondary data carne from the semi structured interviews and enabled an analytical and categorical checking. The samples for the interviews were selected from populations, inside the AMRJ, that were similar to populations of private industries and each person of the population having similar functions to other industries or enterprises in order to be representative for the research. The collected data concluded that the AMRJ is still in a process of changing and that the job became more fulfilling to the tactical leveI, having a challenging and a professional growth perspective, as for the operational leveI it did not mean fulfillment, but frustrating despite their good feelings towards the institution. There is also the conclusion that the change is necessary despite their challenges and if influences the employee's perception, but it may become negative if there isn't a fair distribution of its benefits among all leveIs of the institution.